The effect of free cash flow (FCF) on agency cost and financial performance in financial sector companies registered in indonesia stock exchange (BEI) 2015-2016 - Agung Purnawarman; Puji Handayati (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2021)
The company not only aims to seek profit, but also to maximize the prosperity of its shareholders by maximizing the value of the company. Within the company, there are three people who have different interests, namely, company owners, shareholders, and managers. When the company generates free cash flow, there will be differences in the interests of the parties who make the work contract and create a conflict that will cause the company to pay costs, which is called agency cost. The result of this difference in interest can also affect the company's financial performance because the company's finances are not going well. The purpose of this study was to determine the effect of free cash flow (FCF) on agency cost and financial performance in financial sector companies listed on the IDX in 2015-2016. The type of research used in the research is Explanatory Research, with a population of 83 companies listed on the Indonesian stock exchange in the financial sector in 2015-2016. The sampling technique used the purposive sampling method of as many as 61 companies listed on the Stock Exchange in the financial sector 2015-2016. The analytical tool used in this study is a simple regression test. Based on the results of the analysis, it is found that free cash flow (FCF) has a positive and significant effect on agency cost in financial sector companies listed on the IDX 2015-2016 of 33.7% and free cash flow (FCF) has a positive and significant effect on performance. finance by 34.0%.